2020
DOI: 10.1042/bsr20192051
|View full text |Cite
|
Sign up to set email alerts
|

An updated meta-analysis of the association between fibroblast growth factor receptor 4 polymorphisms and susceptibility to cancer

Abstract: Fibroblast growth factor receptor 4 (FGFR4) is a cell surface receptor tyrosine kinases for FGFs. Several studies have focused on the association between FGFR4 polymorphisms and cancer development. This meta-analysis aimed to estimate the association between FGFR4 rs351855 (Gly388Arg), rs1966265 (Val10Ile), rs7708357, rs2011077, and rs376618 polymorphisms and cancer risk. Eligible studies were identified from electronic databases. All statistical analyses were achieved with the STATA 14.0 software. Pooled odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…FGFR4 SNP, rs351855, has been extensively reported for its association with the occurrence, progression, and prognosis of multiple tumor types [28]. This genetic variation (G > A) causes the substitution of glycine by arginine at position 388 in the transmembrane domain of the receptor [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFR4 SNP, rs351855, has been extensively reported for its association with the occurrence, progression, and prognosis of multiple tumor types [28]. This genetic variation (G > A) causes the substitution of glycine by arginine at position 388 in the transmembrane domain of the receptor [19].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be, in part, accounted for by variations in the allele frequency of FGFR4 arg388 across the general population of different ethnic groups. It was estimated that FGFR4 arg388 has an allele frequency of ~13% in the African population, roughly 30% in the European and Northeast Asian populations, and nearly 45% in the Latino and Southeast Asian (such as Taiwan) populations [28,31]. As such, rs351855 was often demonstrated to be correlated with clinicopathological features of cancer but not with the occurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…When FGFR4 is transphosphorylated, it is activated and induces cell proliferation by stimulating the kinase receptor [ 38 ]. The presence of this arginine stabilizes the protein and prolongs its activity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent meta-analysis by Moazeni-Roodi et al. revealed that the FGFR4 rs1966265 C>T polymorphism significantly reduced the risk of cancer in the recessive model (TT vs CT+CC) and the rs7708357 G>A variant was significantly associated with increased cancer development in the dominant model (AG+AA vs GG) ( 32 ). The Y367C FGFR4 mutation in the extracellular juxtamembrane domain promotes the FGFR4 dimerization on the cell surface and thereby leads to ligand-independent activation of downstream signaling pathways ( 73 ).…”
Section: Discussionmentioning
confidence: 99%